Pengaruh Pemberian Dukungan Emosional oleh Perawat Terhadap Tingkat Kecemasan Pada Pasien Pre Operasi di RSUD Karawang - Artina, A.Ayu; Fitriani, Elfira Sri (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Anxiety is an unclear fear accompanied by feelings of uncertainty, helplessness, isolation, and insecurity. Anxiety is an emotional state without a specific object. Symptoms of anxiety before surgery can be seen from the behavior of patients who look restless, ask questions continuously and even repeatedly even though their questions have been answered. The emergence of anxiety symptoms is caused by internal factors both biologically and psychologically. The level of anxiety of each individual who will undergo surgery is certainly different, some experience mild, moderate, severe anxiety and even panic. Emotional support includes support that is manifested in the form of affection, trust, attention, listening and being heard. Emotional support involves expressions of empathy, attention, encouragement, personal warmth, love, or emotional help. This research was conducted because from the data obtained by researchers in the field, there are still many pre-operative patients who feel anxious when they are going to face surgery because they do not get support from their families and nurses. To determine the effect of emotional support by nurses on anxiety levels in pre-operative patients at Karawang Regional Hospital. The method in this study is analytical correlation with a cross-sectional approach. Sampling using incidental sampling technique of 67 respondents. Data collection using questionnaires. The study was analyzed in 2 stages including univariate analysis and bivariate analysis using SPSS 25 software with the Chi-Square test. From the Chi Square statistical test, a p Value of 0.000 <0.05 α was obtained, so reject Ho and accept Ha, so it can be concluded that there is a Relationship between the Level of Anxiety and the Emotional Support of Nurses in Patients Who Will Undergo Surgery at Karawang Regional Hospital. From the results of the research that has been carried out, there is a Relationship between the Level of Anxiety and the Emotional Support of Nurses in Patients Who Will Undergo Surgery at Karawang Regional Hospital. That the emotional support of nurses plays an important role in a person, especially in pre-operative surgical patients, this is related to the anxiety experienced by patients before undergoing surgery. Keywords: Emotional Support Of Nurses, Anxiety, And Pre-Operative.     ABSTRAK Kecemasan  adalah  rasa  takut  yang  tidak  jelas  disertai  dengan perasaan  ketidakpastian, ketidakberdayaan, isolasi, dan ketidakamanan. Kecemasan adalah keadaan emosi tanpa objek tertentu. Gejala  cemas  sebelum  operasi  dapat  dilihat  dari  tingkah  laku  pasien  yang terlihat gelisah, bertanya terus menerus bahkan berulang- ulang walaupun pertanyaannya telah dijawab.   Timbulnya   gejala   kecemasan diakibatkan oleh  faktor  internal  secara biologis  maupun  psikologis. Tingkat kecemasan masing-masing individu yang akan mendapatkan tindakan pembedahan tentunya berbeda-beda, ada yang mengalami cemas ringan, sedang, berat bahkan panik. Dukungan emosional meliputi dukungan yang diwujudkan dalam bentuk afeksi, adanya kepercayaan, perhatian, mendengarkan dan didengarkan. Dukungan emosional melibatkan ekspresi empati, perhatian, pemberian semangat, kehangatan pribadi, cinta, atau bantuan emosional. Peneliti ini dilakukan karena dari data yang diperoleh oleh peneliti dilapangan, masih banyak pasien   pre operasi yang merasa cemas saat akan menghadapi operasi karena tidak mendapat dukungan dari keluarga dan perawat. Untuk mengetahui pengaruh pemberian dukungan emosional oleh perawat terhadap tingkat kecemasan pada pasien pre operasi di RSUD Karawang. Metode dalam penelitian ini adalah korelasi analitik dengan pendekatan cross sectional. Pengambilan sample dengan teknik incidental sampling sebanyak 67 responden. Pengumpulan data menggunakan kuesioner. Penelitian dianalisis pada 2 tahap diantaranya analisis univariat serta analisis bivariat menggunakan perangkat lunak SPSS 25 dengan uji Chi-Square. Dari uji statistik Chi Square didapat p Value 0,000 < 0,05 α jadi tolak Ho dan terima Ha, maka dapat disimpulkan bahwa ada Hubungan Tingkat kecemasan Dengan  dukungan emosional perawat pada pasien yang akan menjalani operasi di RSUD karawang.Dari hasil penelitian yang telah dilaksanakan bahwa ada Hubungan Tingkat kecemasan Dengan  dukungan emosional perawat pada pasien yang akan menjalani operasi di RSUD karawang. Bahwa dukungan emosional perawat berperan penting pada diri seseorang, terutama pada pasien pra operasi pembedahan, hal ini berkaitan dengan kecemasan yang dialami pasien sebelum menjalani tindakan operasi. Kata Kunci: Dukungan Emosional Perawat, Kecemasan, dan Pre Operasi